Microwave-assisted solvent-free parallel synthesis of thioamides - Olsson, R. ; 0000-0002-7107-3472; Hansen, H. C.; Andersson, C. M. (Tetrahedron Letters, 2000)
Rapid parallel synthesis of thioamides is described. A library of amides, synthesised by mixing acyl chlorides and diamines, was transformed into the corresponding thioamides utilising Lawesson's reagent as the oxygen/sulphur exchange reagent. Purification by solid-phase extraction afforded the library members in adequate purities and yields. (C) 2000 Elsevier Science Ltd.
Keywords: Microwave; Parallel synthesis; Thioamide